UPAYA KEPALA SEKOLAH DALAM PENINGKATAN MUTU DAN KUALITAS SUMBER DAYA MANUSIA (SDM) DI MADRASAH IBTIDAIYAH NEGERI 2 KOTA MALANG - Syarifah, Syarifah; Maymanah, Ratu Meisya; Raudah, Rahma (STKIP Pesisir Selatan, 2025)
One of the principal's responsibilities in improving the quality of education is realized through efforts to develop the quality of teaching staff. This improvement covers aspects of pedagogical, personal, social, and professional competence. In the world of education, improving the quality of teachers plays an important role in producing outstanding students and creating an effective learning process. This study employs a qualitative method with an intrinsic case study design, focusing on the strategies implemented by the principal of State Elementary School 2 in Malang City to enhance human resource quality. Data collection techniques were conducted through in-depth interviews, limited participatory observation, and document analysis (school profiles, work plans, decision letters, meeting minutes, as well as official publications from the Ministry of Religious Affairs and the school's website). The findings of this study indicate that: (1) strategies for improving teacher quality are implemented through various programs such as training, workshops, seminars, lesson studies, internal Subject Teacher Meetings (MGMP), and the use of digital technology; (2) there are supporting factors as well as obstacles that influence the process of improving human resource quality at MIN 2 Kota Malang; (3) The efforts undertaken by the school principal have yielded tangible results and significantly impacted the quality of human resources at the madrasah.